Social Capital of Local Communities in Improving the Economy Through Utilizing the Potential of Sago in the Peatlands of Meranti Islands Regency (Nusantara Science and Technology Proceedings, 2022)
Sago plants located in Tanjung Village and Tanjung Darul Tazim Village, Meranti Islands Regency are one of the centers for sago nurseries located in peatland areas that have the potential to cause land fires. Therefore, this study aims to determine the social capital of local communities in improving the economy through the use of sago plants and how to restore peatlands. Data collection methods used are question and answer, observation, and documentation. The targets of this question-and-answer activity are District Officials, Village Officials, Sago Farmers, Sago Business Actors, Local Community Leaders, and other related parties. The results of this study indicate that sago is proven to be able to improve the family's economy, especially for the local community. The income from sago provides income for the community, both from their plantations and from those who work for other parties. Benefits in the economic field turned out to support the formation of benefits in the social field, namely producing a surau. Also useful in the field of education, namely producing the Al-Manar Education Foundation and increasing their children's education to graduate degrees. Extensive plantations, supportive soil, and good maintenance are the factors that make the Meranti Islands one of the largest sago-producing areas. The way the community restores peatlands here, namely by building canals (tits) around sago plantations, has been praised by President Joko Widodo.